2018
DOI: 10.1002/da.22747
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance in antidepressant-free recurrent major depressive disorder

Abstract: These findings support that processing speed deficits appear in young adults with early onset depression that may not be related to current mood. Additionally, the effects of cumulative depressive episodes may interact with aging such that cognitive performance deficits worsen with recurrence over the lifespan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
5
16
1
1
Order By: Relevance
“…Cronbach’s alpha (CoA) was computed for each domain as a measure of internal consistency. As previously published 28 , for the adult cohort, tests in each domain included: Episodic Memory (CoA = 0.87): Logical Memory 1 and 2 from the Wechsler Memory Scale, Benton Visual Retention Test, Rey’s Verbal Learning Test (total I–V and total VII); Executive Function (CoA = 0.75): Controlled Oral Word Association (COWA) test (letters: C, F, L), Trail Making B time (reverse scored), semantic fluency (Animal Naming), Stroop Color-Word interference condition; Processing Speed (CoA = 0.70): Symbol-Digit Modality, Trail Making A time (reverse scored), Stroop Color Naming condition; Working Memory (CoA = 0.75): Digit Span forward and Digit Span backward from the Wechsler Memory Scale. …”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations
“…Cronbach’s alpha (CoA) was computed for each domain as a measure of internal consistency. As previously published 28 , for the adult cohort, tests in each domain included: Episodic Memory (CoA = 0.87): Logical Memory 1 and 2 from the Wechsler Memory Scale, Benton Visual Retention Test, Rey’s Verbal Learning Test (total I–V and total VII); Executive Function (CoA = 0.75): Controlled Oral Word Association (COWA) test (letters: C, F, L), Trail Making B time (reverse scored), semantic fluency (Animal Naming), Stroop Color-Word interference condition; Processing Speed (CoA = 0.70): Symbol-Digit Modality, Trail Making A time (reverse scored), Stroop Color Naming condition; Working Memory (CoA = 0.75): Digit Span forward and Digit Span backward from the Wechsler Memory Scale. …”
Section: Methodsmentioning
confidence: 96%
“…All study participants provided written informed consent. Data from the adult cohort has previously been reported 28 , 29 and we have also reported cognitive data from the geriatric cohort 20 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, other studies have reported how opioids affect memory, learning, and emotional disturbances (2, 3, 10, 11). Depression has long been associated with widespread cognitive deficits (12) which tend to worsen over a life span (13).…”
Section: Introductionmentioning
confidence: 99%